Effect of Cashless Policy and Its Implication on Agricultural Activities of Rural Farmers in Ogun State, Nigeria - Damilola Olaide Badru; Adekunle Stephen Adeoye; Victor Edoh Odeje; Oluwagbemileke Babasegun Omoyinmi (Interdisciplinary Journal Of Lifelong Learning, 2025)
This study analysed the effects of cashless policy and its implication on agricultural activities of rural farmers in Ogun State, Nigeria. Multi-stage sampling procedure was used to select 240 respondents, while interview schedule was used to obtain primary data. Data were analysed using frequency, percentage, mean, and Pearson’s Product Moment Correlation (PPMC) at p=0.05. The results revealed that respondents had an average of 55years of age, 75.0% were male, 4 persons per household, had an average of 19years of farming experience, and 2.53 hectares of farm size. The effects of cashless policy were positively seen among rural farmers as majority of them responded to all statements. There is moderate (56.7%) perception towards the utilization of cashless policy among rural farmers. Some of the problems facing rural farmer towards cashless policy were political/economic instability (x̄= 2.17), lack of digital literacy (x̄= 2.03) and lack of access to technology/infrastructure (x̄= 2.00). The coping strategies were the use of trade by barter most times (95.8%), utilisation of POS services (87.5%) and digital payment such as moniepoint (83.3%). Significant correlation (p < 0.05) exists between the impacts of the cashless policy (r = 0.682, p > 0.011) and the perceptions of rural farmers regarding the implementation of the cashless policy within the designated study area. The study concluded that the cashless policy had brought about significant effects and is gradually delivering the intended benefits to the rural farmers and the people of Nigeria, particularly those in remote areas.